Electrochemically driven optical and SERS immunosensor for the detection of a therapeutic cardiac drug. Issue 5 (20th January 2022) - Chaudhry, Madeeha; Lim, Dong-Kwon; Kang, Jeon Woong; Yaqoob, Zahid; So, Peter; Bhopal, Muhammad Fahad; Wang, Minqiang; Qamar, Raheel; Bhatti, Arshad Saleem
Abstract : Cardiovascular diseases pose a serious health risk and have a high mortality rate of 31% worldwide. Abstract : Cardiovascular diseases pose a serious health risk and have a high mortality rate of 31% worldwide. Digoxin is the most commonly prescribed pharmaceutical preparation to cardiovascular patients particularly in developing countries. The effectiveness of the drug critically depends on its presence in the therapeutic range (0.8–2.0 ng mL −1 ) in the patient's serum. We fabricated immunoassay chips based on QD photoluminescence (QDs-ELISA) and AuNP Surface Enhanced Raman Scattering (SERS-ELISA) phenomena to detect digoxin in the therapeutic range. Digoxin levels were monitored using digoxin antibodies conjugated to QDs and AuNPs employing the sandwich immunoassay format in both the chips. The limit of detection (LOD) achieved through QDs-ELISA and SERS-ELISA was 0.5 ng mL −1 and 0.4 ng mL −1, respectively. It is demonstrated that the sensitivity of QDs-ELISA was dependent on the charge transfer mechanism from the QDs to the antibody through ionic media, which was further explored using electrochemical impedance spectroscopy. We demonstrate that QDs-ELISA was relatively easy to fabricate compared to SERS-ELISA. The current study envisages replacement of conventional methodologies with small immunoassay chips using QDs and/or SERS-based tags with fast turnaround detection time as compared to conventional ELISA.